2012
DOI: 10.1152/ajprenal.00692.2011
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin-sensitive adenylyl cyclases mediate AVP-dependent cAMP production and Clsecretion by human autosomal dominant polycystic kidney cells

Abstract: In autosomal dominant polycystic kidney disease (ADPKD), binding of AVP to the V2 receptor (V2R) increases cAMP and accelerates cyst growth by stimulating cell proliferation and Cl(-)-dependent fluid secretion. Basal cAMP is elevated in human ADPKD cells compared with normal human kidney (NHK) cells. V2R mRNA levels are elevated in ADPKD cells; however, AVP caused a greater increase in global cAMP in NHK cells, suggesting an intrinsic difference in cAMP regulation. Expression, regulatory properties, and recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
(156 reference statements)
2
25
0
Order By: Relevance
“…A recent study found that, although cAMP was elevated in PKD cells obtained from human kidneys (compared with normal human kidney [NHK] cells), AVP causes a greater increase in NHK cell cAMP, 16 suggesting that the total amount of cellular cAMP is less important than its localized effects within the cell. Inhibition of calmodulin, which reduces AC6 and AC3 activity, decreased AVP-induced cAMP in PKD but not NHK cells.…”
mentioning
confidence: 99%
“…A recent study found that, although cAMP was elevated in PKD cells obtained from human kidneys (compared with normal human kidney [NHK] cells), AVP causes a greater increase in NHK cell cAMP, 16 suggesting that the total amount of cellular cAMP is less important than its localized effects within the cell. Inhibition of calmodulin, which reduces AC6 and AC3 activity, decreased AVP-induced cAMP in PKD but not NHK cells.…”
mentioning
confidence: 99%
“…Although this observation was in agreement with rodent models of hereditary PKD, in which renal cAMP levels were shown to be higher than normal, [20][21][22]36 the cell culture studies suggest that there is also an intrinsic difference in cAMP regulation, leading to higher cAMP levels in ADPKD cells. This, together with our earlier work showing that global PDE inhibition increased cAMP to similar levels in ADPKD and NHK cells, 12 led us to explore specific PDE isoform expression levels and activities in NHK and ADPKD kidneys to determine the underlying basis for this effect. There are .50 isoforms in the PDE superfamily that regulate cAMP and cGMP levels.…”
Section: Discussionmentioning
confidence: 91%
“…ADPKD cells have higher basal cAMP levels compared with NHK cells (Table 1). 12 Vinpocetine and cilostamide significantly increased cAMP in NHK, but not ADPKD cells; by contrast, rolipram increased cAMP in both cells. The effect of 8-MeOM-IBMX, a potent PDE1 inhibitor, was similar to that of vinpocetine (Supplemental Figure 2).…”
Section: Effect Of Pde Inhibition On Intracellular Camp Levelsmentioning
confidence: 88%
See 2 more Smart Citations